2016
DOI: 10.1084/jem.20160635
|View full text |Cite
|
Sign up to set email alerts
|

UNG protects B cells from AID-induced telomere loss

Abstract: Verdun and colleagues find that the uracil-DNA glycosylase UNG, which promotes DNA breaks in the immunoglobulin genes during class switch recombination and is required for AID-induced chromosomal translocations, protects telomeres from AID-induced DNA damage and subsequent dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 60 publications
1
33
1
Order By: Relevance
“…However, as no method is available to discriminate between uracil and hmU in specific genomic regions, we do not know which SMUG1 substrate gives rise to these phenotypes in MEFs. Faithful BER of U has been shown to be needed to protect telomeres from unsolicited activation of mismatch repair at U:G pairs generated by activation-induced deaminase, leading to resection of the Crich strand in Ung À/À B cells (Cortizas et al, 2016). We could not detect expression of AID in the HAP1 cells, but we cannot exclude the possibility that AID activation at one stage during establishment of the SMUG1-KO cell line is a cause of the extremely short telomeres in this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…However, as no method is available to discriminate between uracil and hmU in specific genomic regions, we do not know which SMUG1 substrate gives rise to these phenotypes in MEFs. Faithful BER of U has been shown to be needed to protect telomeres from unsolicited activation of mismatch repair at U:G pairs generated by activation-induced deaminase, leading to resection of the Crich strand in Ung À/À B cells (Cortizas et al, 2016). We could not detect expression of AID in the HAP1 cells, but we cannot exclude the possibility that AID activation at one stage during establishment of the SMUG1-KO cell line is a cause of the extremely short telomeres in this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…• Extended replicative potential: Upregulation of telomerase expression, [26][27][28] and protection against AICDA off-target shortening of telomeres by the uracil-DNA glycosylase (UNG) 29 provide GC B cells with improved replicative capacity.…”
Section: G C B Cell S Inherently Fe Ature Hallmark S Of Malig Nant mentioning
confidence: 99%
“…Notably, the ROS-induced DNA damage could in turn cause the generation of more ROS, resulting in a malignant injury cycle 46 . The analysis of genes downstream of TFs further demonstrated that YXS strongly activated the DNA repair system, as indicated by the elevated expression of DNA repair-related genes, such as Pen1, Pole, Eme1, Ung 47 , Dtl 48 , Ssrp1 and Mcm10 49 . Taken together, these results indicated YXS activated biological processes such as anti-apoptotic process and DNA repair to prevent H 2 O 2 -induced damage.…”
Section: Discussionmentioning
confidence: 97%